Performance of a Non Linear Dynamic Vibration Absorbers. (13th November 2014) - Djemal, F.; Chaari, F.; Dion, J.-L.; Renaud, F.; Tawfiq, I.; Haddar, M.
Abstract : The most common method of vibration control is the use of the dynamic absorbers. Two types of absorbers can be found: Linear and nonlinear. The use of linear absorbers allows reducing vibration but only at the resonance frequency, whereas nonlinear absorbers attenuate vibration on a wide band of frequency. In this paper, a nonlinear two degrees of freedom (DOF) model is developed. A cubic nonlinearity induced by a gap is considered. The objective of the paper is to characterize nonlinear vibration of the system by applying explicit formulation (EF). An experimental study is performed to validate the numerical results. The jump phenomenon is the principal nonlinear dynamic phenomenon observed on both numerical and experimental investigations.